The Role of the Catholic Church in Supporting Local Government's Policy on Tourism Development in West Flores - Fransiska Widyawati (ARISTO, 2022)
Tourism has become one of the prime movers of development in NTT, especially in West Flores. Local government cannot be a single fighter in promoting tourism. Developing tourism requires the government to collaborate with private sector. This article explores the role of the Ruteng Diocese Catholic Church in supporting tourism development in West Flores. The data collection method used was a study of Church documents, field studies through participatory observation of church and government activities, interviews and discussions with relevant parties. This research is focused on the collaboration of the Church and Government in 2022. This research concludes that the Catholic Church has played a significant role in supporting the regional government in promoting tourism in West Flores. Support was carried out in various forms, such as spiritual support through prayer and worship as well as in the form of concrete programs to strengthen tourism knowledge, giving an ethical and moral to tourism development so that it has a holistic dimension, doing seminars and workshops, promoting wealth and tourist sites, supporting the development of the creative economy, maintaining culture, and organizing tourism festivals. This research concludes that the Catholic Church has a significant role in promoting tourism in West Flores. This research recommends the local government faithfully collaborate with the Church. The collaboration also needs to be expanded to other institutions, including other religious institutions and other social institutions such as tourism actors, indigenous peoples, and non-governmental organizations.